2008
DOI: 10.1007/s00424-008-0611-5
|View full text |Cite
|
Sign up to set email alerts
|

The liver and kidney expression of sulfate anion transporter sat-1 in rats exhibits male-dominant gender differences

Abstract: The sulfate anion transporter (sat-1, Slc26a1) has been cloned from rat liver, functionally characterized, and localized to the sinusoidal membrane in hepatocytes and basolateral membrane (BLM) in proximal tubules (PT). Here, we confirm previously described localization of sat-1 protein in rat liver and kidneys and report on gender differences (GD) in its expression by immunochemical, transport, and excretion studies in rats. The ∼85-kDa sat-1 protein was localized to the sinusoidal membrane in hepatocytes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 50 publications
3
40
0
Order By: Relevance
“…The SO 4 2-/anion exchange system that transports various anions including oxalate was demonstrated in the sinusoidal (114,115,121 membrane of rat hepatocytes (129). In support of these fi ndings, Sat-1, an exchanger of SO 4 2-and an oxalate, was localized in rats to the hepatocyte sinusoidal membrane (116,117,130). Recent transport studies on Sat-1 expressing oocytes demonstrated that Sat-1 can exchange SO 4 2-or HCO 3 -for oxalate in both directions, but the affi nity for oxalate is lower than for counter anions.…”
Section: Oxalate-handling Transporters and Their Role In Hyperoxalurimentioning
confidence: 59%
See 3 more Smart Citations
“…The SO 4 2-/anion exchange system that transports various anions including oxalate was demonstrated in the sinusoidal (114,115,121 membrane of rat hepatocytes (129). In support of these fi ndings, Sat-1, an exchanger of SO 4 2-and an oxalate, was localized in rats to the hepatocyte sinusoidal membrane (116,117,130). Recent transport studies on Sat-1 expressing oocytes demonstrated that Sat-1 can exchange SO 4 2-or HCO 3 -for oxalate in both directions, but the affi nity for oxalate is lower than for counter anions.…”
Section: Oxalate-handling Transporters and Their Role In Hyperoxalurimentioning
confidence: 59%
“…As shown in Fig. 4, in rat kidneys the Sat-1 protein was localized by immunochemical methods to the proximal tubule BLM (117,118).…”
Section: Figure 3 Transporters Along the Rodent Gastrointestinal Tracmentioning
confidence: 83%
See 2 more Smart Citations
“…However, the treatment of tissue cryosections with sodium dodecyl sulfate (SDS), without heating, has been efficiently used to enhance immunostaining with some antibodies (Brown et al, 1996;Sabolić et al, 1999), thus indicating that unmasking techniques may be beneficial for revealing the antibody binding epitopes also in cryosections. Furthermore, we have recently described that heating cryosections of the PFAfixed rat and mouse organs in a microwave oven can be used to enhance immunostaining with specific antibodies for various transporters of organic anions (Bahn et al, 2005;Breljak et al, 2010;Brzica et al, 2009b;Ljubojević et al, 2004Ljubojević et al, & 2007Yokoyama et al, 2008), glucose (Balen et al, 2008;Sabolić et al, 2006), and sulfate (Brzica et al, 2009a). In order to demonstrate the importance of various unmasking protocols for immunocytochemical studies in tissue cryosections, we have used cryosections of the rat kidney and liver tissues that had been fixed with 4% PFA in vivo, treated them with various antigen retrieval protocols without and with the use of microwave heating, and tested for the intensity of immunostaining of several representative proteins known to reside in the cell membrane (cell adhesion molecule 105 (CAM105), megalin (GP 330 ), Na/K-ATPase, aquaporin 1 (AQP1)), cytoplasm (metallothionein), cell membrane and intracellular organelles (vacuolar H + -ATPase (V-ATPase)), and cytoskeleton (actin, tubulin).…”
mentioning
confidence: 99%